Hubungan Nokturia dengan Kualitas Tidur pada Mahasiswa Profesi Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Brawijaya selama Pandemi Covid-19 - Rahmaniar, Fathina Zahrani; Daryanto, Besut; Rakhmani, Alidha Nur (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: Nocturia defined as an individual's complaint of having an urge to urinate during the night, followed by sleep. It is particularly happened in young adults who have a heavy workload. Clinical year students are among the populations with high levels of physical fatigue and stress, which may lead to sleep disorders that might impair the quality of one's sleep. Particularly recently, the Covid-19 pandemic is affecting many parts of people's life, such as the implementation of a lecture system and limitations on the number of hours that clinical year students in Indonesia can work. Aim: The purpose of this study is to determine the prevalence of nocturia, the quality of their sleep, and the correlation between those two in clinical year students in the Faculty of Medicine at Universitas Brawijaya during the Covid-19 pandemic. Methods: This is an analytic observational study with cross sectional design and purposive sampling method. This study was conducted in April and May of 2022. According to inclusion and exclusion criteria, 78 clinical year students were selected as the participants in the study. Data analyzed with the Chi-square test for univariate and bivariate data analysis. Results: Among the 78 respondents, 39 (50%) reported having nocturia and 47 (60.30%) reported having poor sleep quality. The chi-square probability value for the test of the correlation between nocturia and sleep quality was 0.488 (p>0.05). Conclusion: Clinical year students frequently have poor sleep quality and nocturia symptoms. However there is no association between nocturia and sleep quality.